UPAYA MENINGKATKAN TANGGUNG JAWAB BELAJAR SISWA KELAS VII G MELALUI LAYANAN KONSELING KELOMPOK DENGAN MEDIA SELF JOURNEY CHEST DI SMP NEGERI 8 BANJARMASIN - Ulfia Nurul Anisa; Putri Delima; Desy Purnama Putri; Sulistiyana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low level of learning responsibility among students of class VII G at SMP Negeri 8 Banjarmasin. This condition was reflected in several behaviors, including the need for frequent reminders to complete assignments, inability to explain the reasons behind their learning activities, a tendency to blame others for learning difficulties, lack of enthusiasm in completing tasks independently, weak interest in learning, and difficulty maintaining concentration during learning activities. The pre-test results showed an average learning responsibility score of 25.50, with five students categorized as low and three students categorized as moderate. This study aimed to describe the implementation of group counseling services using the Self Journey Chest media to improve learning responsibility and to examine the effectiveness of the service in enhancing students’ learning responsibility. This research employed Guidance and Counseling Action Research (PTBK), conducted in three cycles by adapting the Kemmis and McTaggart model. The research subjects consisted of eight students from class VII G who were identified as having low learning responsibility based on the needs assessment results. Data were collected through a learning responsibility questionnaire, observation sheets, and student worksheets. The data were analyzed using quantitative and qualitative comparative descriptive approaches. The findings indicated a significant improvement in students’ learning responsibility across each cycle. The average score increased from 25.50 in the pre-cycle stage (low category) to 29.00 in Cycle I (moderate category), 40.50 in Cycle II (high category), and 53.38 in Cycle III (very high category). By the end of Cycle III, all students (100%) achieved high or very high levels of learning responsibility, exceeding the predetermined success indicator of 75%. Therefore, group counseling services utilizing the Self Journey Chest media were proven effective in improving the learning responsibility of class VII G students at SMP Negeri 8 Banjarmasin.